Nation Branding in the Americas Contested Politics and Identities - Sevin, Efe (Routledge Focus on Nation Branding Series, 2025)
This book provides an overview of nation branding in the Americas, an often neglected continent(s) in debates about the creation, dissemination and management of national images. It will particularly be of interest for students and researchers specialized in marketing, media and communication, and international relations